Hyperechoic lesions of aortic valves on the short axis view of echocardiography in patients undergoing hemodialysis - Nagano, Masashi; Tagawa, Hitoshi; Umezu, Michio; Yamakado, Minoru; Takano, Tomoko (Journal of Japanese Society for Dialysis Therapy, 1989)
We evaluate hyperechoic lesions of the aortic valves using the short axis view of echocardiography in 157 patients undergoing maintenance hemodialysis, including with diabetic nephropathy. Their ages ranged from 20 to 76 years, with a mean of 49.8 years. They had been receiving dialysis for between 5 months, and 13 years and 7 months (mean, 6 years and 5 months). Patients with ischemic heart disease as confirmed by coronary angiography and patients diagnosed with echocardiography as having no heart disease were also studied as controal subjects. Hyperechoic lesions were observed in 69 dialysis patients (43.9%), a frequecy similar to the control subjects. The lesions in dialysis patients were mild except for two moderate and one severe lesions. Severe aortic regurgitation was not observed in any patient. The frequency of hyperechoic lesions increased with age in the control subjects, but was similar throughout all age groups in the dialysis patients, probably bocause many hyperechoic lesions were observed in dialysis patients younger than 50 years old. The frequency of hyperechoic lesions was not correlated with the period of dialysis, administration of alfacalcidol, dialysate buffer (acetate/bicarbonate), history of hypertension and smoking, or average predialysis serum concentrations of calcium, inorganic phosphorus, parathyroid hormone and total cholesterol during 2 1/2 years before echocardiography. However, this study could not elucidate whether the hyperechoic lesions originated from sclerotic or calcified changes in the aortic valves.